Main causes of medication administration errors among final year student nurses in University College of Islam Melaka (KUIM) - Mohd Noh, Hairanni; Seng, Soong Chong; Mohamed Ludin, Salizar; Mohamed Ariffin, Suzilawati (Scholars Academic and Scientific Publisher, 2018)
Medication errors can occur at any stage of medication administration includes: ordering, transcribing, dispensing, administering and also monitoring. The most common factors are physician communication, knowledge, attitude, and rights violations. However, some circumstances may increase the chance of their involvement in medication errors, especially for an undergraduate nursing student. The purpose of the study is to investigate and to find out the main causes leading to medication administration errors among final year nursing students in University College of Islam Melaka (KUIM).A cross-sectional study and convenience sampling method were used to select the sample. Ninety-eight respondents involved in the study and the data was collected using a self-administrative questionnaire. The researcher comes out with result that the most popular causes that contribute to medication administration error were right violations (mean: 35.53, SD: 6.26) followed by knowledge (mean: 32.03, SD: 6.42), attitude of the students (mean: 22.62, SD: 2.97) and physician communication (mean: 20.88, SD: 5.41). Administration of medication is the most important part of patient safety, and medication errors should be reported and avoided. This is very important for third-semester nursing students to take full consideration and best practice to avoid medication errors before their graduates and become a registered nurse.